2016
DOI: 10.1261/rna.054890.115
|View full text |Cite
|
Sign up to set email alerts
|

The yjdF riboswitch candidate regulates gene expression by binding diverse azaaromatic compounds

Abstract: The yjdF motif RNA is an orphan riboswitch candidate that almost exclusively associates with the yjdF protein-coding gene in many bacteria. The function of the YjdF protein is unknown, which has made speculation regarding the natural ligand for this putative riboswitch unusually challenging. By using a structure-probing assay for ligand binding, we found that a surprisingly broad diversity of nitrogen-containing aromatic heterocycles, or "azaaromatics," trigger near-identical changes in the structures adopted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 65 publications
1
50
0
Order By: Relevance
“…Members of the second riboswitch class respond to a diverse collection of multi-ring molecules that can best be called "azaaromatic" ligands, and thus these RNAs are called azaaromatic riboswitches (Li et al 2016). Within the genomic DNA database used for our study, 743 representatives of azaaromatic riboswitches were identified, which suggests that members of this class sense a natural compound that is of wide importance to bacteria.…”
Section: Riboswitches For Amino Acids and Other Metabolitesmentioning
confidence: 87%
“…Members of the second riboswitch class respond to a diverse collection of multi-ring molecules that can best be called "azaaromatic" ligands, and thus these RNAs are called azaaromatic riboswitches (Li et al 2016). Within the genomic DNA database used for our study, 743 representatives of azaaromatic riboswitches were identified, which suggests that members of this class sense a natural compound that is of wide importance to bacteria.…”
Section: Riboswitches For Amino Acids and Other Metabolitesmentioning
confidence: 87%
“…For the first approach, extremely rare gene associations were considered, as they hinted that the ligand might have some connection to nicotinamide adenine dinucleotide (NAD + ) or FMN metabolism. These coenzymes and their derivatives were examined for in vitro binding to yjdF RNAs, which unexpectedly revealed that diverse flavin analogs are bound by yjdF RNAs with relatively high affinity (Li et al 2016). Mutations to highly conserved nucleotides disrupt Cold Spring Harbor Laboratory Press on July 31, 2020 -Published by rnajournal.cshlp.org Downloaded from associations with these ligands, indicating that this promiscuous binding was unlikely to be due to non-specific interactions.…”
Section: Yjdf Motif Rnas: Azaaromatic Riboswitchesmentioning
confidence: 99%
“…Specifically, a B. subtilis riboswitch-reporter strain was grown in ~2,000 conditions sampled by a growth media library. Only five supplemented compounds triggered the yjdF RNA-lacZ reporter, all of which were large, planar, nitrogenous, polycyclic molecules (Li et al 2016). The hits from the screen, as well as the flavin derivatives identified through additional binding assays, share little resemblance with one another except that they all fall into the general category of 'azaaromatic' molecules.…”
Section: Yjdf Motif Rnas: Azaaromatic Riboswitchesmentioning
confidence: 99%
“…) and azaaromatic compounds (Li et al . ), a long lag could be harmful to the cell. Furthermore, it has been shown that aptamer folding depends on physiological conditions (Chen et al .…”
Section: Riboswitchesmentioning
confidence: 99%